FEED EFFICIENCY AND GROWTH OF CATFISH (Clarias sp.) FED WITH THE ADDITION OF IMMUNE-BOOSTING FERMENTED EARTHWORMS - Mukhlisnah Djalil; Alim Isnansetyo; Triyanto Triyanto; Tito Arya Nugraha (Indonesian Aquaculture Journal, 2022)
A fermented earthworm (FEW) is reported to be an alternative to an immune-modulator feed additive in catfish. However, the effects on growth and feed efficiency have not been reported yet. The present study aimed to evaluate the effects of fermented earthworms (FEW) on the growth and feed efficiency of catfish (Clarias sp.). A feeding trial was conducted in a completely randomized design with five treatments of diet in quadruplicate. The trial was conducted for 78 days. The observed parameters comprised of survival rate (SR), specific growth rate (SGR), feed conversion ratio (FCR), feed efficiency (FE), protein efficiency ratio (PER), and total biomass. The results revealed that the FEW at up to 5% did not affect (P>0.05) the growth rate of catfish, but FEW gave a negative effect on the growth rate (P>0.05) at the addition rate higher than 5%. The highest growth rate was found at the addition rate of 2.5%. FEW also did not affect the survival rate (SR), FCR, PER, and total biomass (P>0.05). This study successfully confirmed that FEW could be used as an alternative to immuno-modulator ingredient without any negative impact on the growth of catfish when FEW was added to the feed at as high as 5%. These findings give a new perpective in utilizing FEW as a fuctional aqua-feed ingredient to increase immune response without alteration of the fish growth.